2022
DOI: 10.18502/ijps.v17i4.10696
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Severity of the COVID-19 Disease, Temperament and Psychological Factors

Abstract: Objective: The coronavirus (COVID-19) pandemic negatively affects public mental health around the world. Individuals’ reactions to COVID-19 vary depending on their temperament, individual differences, and personality traits. Therefore, the current study is conducted to assess the association of demographical features, Persian temperament, and psychological characteristics with the severity of COVID-19. Method: An online survey was sent to COVID-19 patients to collect their demographic information, COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A higher score shows more severe depressive symptoms. An appropriate reliability value, test-retest reliability coefficient and internal consistency have been reported for this questionnaire in Peru ( 24 ) and other countries such as Iran ( 25 ).…”
Section: Methodsmentioning
confidence: 91%
“…A higher score shows more severe depressive symptoms. An appropriate reliability value, test-retest reliability coefficient and internal consistency have been reported for this questionnaire in Peru ( 24 ) and other countries such as Iran ( 25 ).…”
Section: Methodsmentioning
confidence: 91%
“…The study of phytochemicals against SARS-CoV-2 M pro is most important at the time where there is still an ongoing number of infected cases and deaths reported due to increasing rate of mutations in the spike protein of SARS-CoV-2 [ 40 ], which renders vaccination less effective [ 41 ]. Additionally, the concept of temperament is highly important and can affect the severity of a disease as reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that the coldness (and wetness) of the brain i.e. having a cold temperament, was associated with the severity of the COVID-19 infection and hence regarded as a factor to be considered in preventing the disease or in predicting the course of the disease [ 26 ].…”
Section: Introductionmentioning
confidence: 99%